2004
DOI: 10.1016/j.femsec.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and distribution of periphytic Synechococcus spp. in biofilms and picoplankton of Lake Constance

Abstract: In various water depths of the littoral zone of Lake Constance (Bodensee) cyanobacteria of the Synechococcus-type were isolated from biofilms (periphyton) on three natural substrates and an artificial one (unglazed tiles). From one tile three strains of phycoerythrin (PE)-rich Synechococcus spp. were isolated, the first examples of these organisms in the epibenthos. Phylogenetic inference based on the 16S-23S rRNA intergenic spacer (ITS-1) assigned all periphytic isolates to two clusters of the picophytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 31 publications
3
50
2
Order By: Relevance
“…Similar low taxa richness of picocyanobacterial (20) and the total bacterial (44) communities in Tibetan lakes was also described. These results contrast with previous observations of diverse picocyanobacterial lineages in other lakes at lower elevations, such as Lake Constance (ϳ400 m above sea level) (17), Lake Mondsee (ϳ500 m) (16), Lake Superior (ϳ180 m) (22), and the Great Mazurian Lakes (ϳ110 m) (21), or in the brackish Baltic Sea (18,19). Evidence also showed that individual water bodies can harbor a diverse range of picocyanobacteria (27).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Similar low taxa richness of picocyanobacterial (20) and the total bacterial (44) communities in Tibetan lakes was also described. These results contrast with previous observations of diverse picocyanobacterial lineages in other lakes at lower elevations, such as Lake Constance (ϳ400 m above sea level) (17), Lake Mondsee (ϳ500 m) (16), Lake Superior (ϳ180 m) (22), and the Great Mazurian Lakes (ϳ110 m) (21), or in the brackish Baltic Sea (18,19). Evidence also showed that individual water bodies can harbor a diverse range of picocyanobacteria (27).…”
Section: Discussioncontrasting
confidence: 89%
“…Prochlorococcus, the cluster 5 Synechococcus, and Cyanobium form a tightly clustered phylogenetic group (3,13), sometimes called the "Syn/Pro clade" (14), the "PS clade" (13), or "group 6b" (5). However, many nonmarine picocyanobacterial lineages (clusters) found in freshwater or brackish environments fell into this group (5,(15)(16)(17) (Table 1 shows a summary). A few of these clusters were widely found in both freshwater lakes and the brackish Baltic Sea, such as the C. gracile cluster, subalpine cluster I, subalpine cluster II, group I, and the LBP1 cluster (5,15,16,18,19), supporting the high dispersive potential of microbes.…”
mentioning
confidence: 99%
“…strains examined in this study were isolated in the year 2000 from two series of tiles (samples were collected from the beginning of March to mid of April and from end of August to mid of October) placed for six weeks at different water depths (7.0, 1.0, and 0.5 m) in the littoral zone of Lake Constance (47° 41′N 09° 07′E, 476 km 2 , maximal depth 254 m), a large oligotrophic prealpine fresh water lake in Germany (details in [22]). As proposed previously [22], we refer to these strains as epibenthic (collected from submerged tiles) in order to distinguish them from pelagic (free-living), epiphytic (collected from macrophytes) or epilithic (collected from stones). Four of these strains were PC-rich (PC1-1, PC2-1, PC3-0.5, and PC4-0.5) and three were PE-rich (PE1-7, PE2-7, and PE3-7).…”
Section: Methodsmentioning
confidence: 99%
“…The number after the dash indicates the water depth from which the strain was originally collected (Table 1). Since the year 2000, non-axenic cultures (co-culture with heterotrophic bacteria) of these strains were grown on solidified BG 11 medium (with nitrate) and BG 11o , a medium with a low concentration of combined nitrogen due to the omission of nitrate, under controlled laboratory conditions at 19°C and a white light regime of 12 h light/12 h dark at a light intensity of 8 to 10 µmol photons·m −2 ·s −1 as described [22]. For experiments, colonies were picked and transferred to BG 11/N liquid medium [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation